STRATEGI MENGEMBANGKAN RESILIENSI INDIVIDU DI TENGAH MASA PANDEMI COVID-19 MENGGUNAKAN ISLAMIC ART THERAPY [STRATEGY TO DEVELOP INDIVIDUAL RESILIENCE IN THE MIDDLE OF THE COVID-19 PANDEMIC USING ISLAMIC ART THERAPY] - R Rahmanisa; Hayatul Khairul Rahmat; Irza Cahaya; Octari Annisa; Suandara Pratiwi (Journal of Contemporary Islamic Counselling, 2021)
The COVID-19 pandemic has become a stressor for individuals today which results in the emergence of various psychological problems such as anxiety, fear, and stress. So that psychological problems are not experienced, it is necessary to make efforts to develop individual resilience. Resilience is the individual's ability to survive and rise from the problems that are happening in his life. Efforts to develop individual resilience during the COVID-19 pandemic can be done by utilizing Islamic Art Therapy. This paper uses a literature study approach using content analysis. Through the use of Islamic Art Therapy it can effectively develop individual resilience during the COVID-19 pandemic.